Merged phytosociological and geographical approach for multiple scale vegetation mapping as a baseline for public environmental policy in Mexico. Issue 3 (21st July 2021) - Velazquez, Alejandro; Medina‐García, Consuelo; Gopar‐Merino, Fernando; Duran, Elvira; Pérez‐Vega, Azucena; Mas, Jean‐François; Giménez de Azcarate, Joaquín; Blanco‐García, Arnulfo; López‐Barrera, Faustino; Castro‐López, Valerio; Aguirre, Rocío
Abstract: Questions: What is the potential use of maps derived from a merged geographical and phytosociological approach to support the design of public environmental policies? Do these approaches and data sources deliver complementary land‐cover/vegetation maps? Objective: The present article documents a joint phytosociological and geographical approach to improve vegetation cartography in temperate‐tropical transitional ecosystems. Location: The research was conducted at national (Mexico) and state (Michoacán) scales. Mexico and Michoacán have been recognized as regions of high eco‐geographical complexity, where temperate‐tropical conditions intermingle, creating large eco‐socio‐cultural mosaics. Methods: Data from 268 field verification sites and 223 relevés surveyed during the last two decades and recent land cover sources were used as the main inputs. The results were further validated by three workshops with local botanists and field verification during 2021. Results: At the national level, Mexico's forests, shrubs, herbs, and non‐vascular major formation classes were hierarchically split by dominant life forms and prevailing climatic affiliations. At the state level, these major formation classes split into 19 sub‐formations, of which 15 were forest communities. Conclusions: We discuss the scientific challenge of transitioning from land cover into vegetation maps and (dis)similarities of approaches reviewing concepts and analytical (quanti)qualitative instruments. The paper contrasts the present output with the experiences of other countries such as Canada, the United States, Bolivia, and Colombia. Finally, the results are discussed in light of their relevance for constructing public environmental policies, such as land use planning, establishment of protected areas, allocation of incentives for sustainable environmental services, and long‐term conservation practices. Abstract : We discuss the scientific challenge of transitioning from land cover into vegetation maps and (dis)similarities of approaches reviewing concepts and analytical (quanti)qualitative instruments. The paper contrasts the present output with the experiences of other countries such as Canada, the United States, Bolivia, and Colombia. Finally, the results are discussed in light of their relevance for constructing public environmental policies, such as land use planning, establishment of protected areas, allocation of incentives for sustainable environmental services, and long‐term conservation practices.